2022
DOI: 10.1186/s12245-022-00421-9
|View full text |Cite
|
Sign up to set email alerts
|

Stoma-related complications and emergencies

Abstract: Stoma creations are common procedures in surgical specialties. They can be created either as a temporary or a permanent measure. Despite advancements in surgical technique and stoma care, complications are common. Patients experiencing stoma-related complications often present to the emergency department. Emergency physicians are not expected to be stoma experts, yet they are often the first point of contact for patients experiencing stoma-related complications. Accordingly, emergency physicians should be fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
(119 reference statements)
0
27
0
2
Order By: Relevance
“…Liu et al 14 On the one hand, high-output stomas are often associated with extensive small bowel resections, in which less than 200 cm are preserved. 7,11,15 Therefore, patients presenting jejunostomies are at high risk of developing a high-output stoma due to an anatomical short bowel syndrome. On the other hand, patients without bowel shortness can also present high-output stomas caused by radiation or infectious enteritis, intra-abdominal sepsis, Crohn disease activity, sudden cessation of corticosteroids, or the use of prokinetic drugs.…”
Section: High-output Stomamentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al 14 On the one hand, high-output stomas are often associated with extensive small bowel resections, in which less than 200 cm are preserved. 7,11,15 Therefore, patients presenting jejunostomies are at high risk of developing a high-output stoma due to an anatomical short bowel syndrome. On the other hand, patients without bowel shortness can also present high-output stomas caused by radiation or infectious enteritis, intra-abdominal sepsis, Crohn disease activity, sudden cessation of corticosteroids, or the use of prokinetic drugs.…”
Section: High-output Stomamentioning
confidence: 99%
“…This process can unquestionably be very irritative and toxic for the skin, and will perpetuate damage and morbidity. 7,16 Therefore, a valid method to avoid these complications may be attaching a spout measuring 2 cm to 3 cm to the ileostomy and avoiding any direct contact between the fluid and the skin. Furthermore, surgeons should aim to create a well-elevated stoma.…”
Section: Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine whether the outlet is stenotic or obstructive, clinicians can simply insert their fingers into the stoma[ 23 ]. An abdominal CT scan or contrast enema study through the stoma may be useful for precise diagnosis, as they can demonstrate the location responsible for SOO/SRO and exclude other sites of SBO (Figures 1 and 2 ).…”
Section: Obstructive Complicationsmentioning
confidence: 99%
“… 9–12 Moreover, proper functioning needs continued care for several physiological reasons including skin inflammation, electrolyte imbalances, stoma necrosis and parastomal hernias, and retraction or prolapse. 13 , 14 In a study interviewing 11 patients living with urostomy identified six themes that described their perception of the major concerns including 1) surgery impact, 2) body image, 3) daily and social-life activities, 4) stoma and sexuality, 5) managing stoma education, 6) family and friends’ support. 15 Hence, enhanced nursing care and nursing-patient interaction based on the scientific research is essential to assist these patients and achieve a better quality of life.…”
Section: Introductionmentioning
confidence: 99%